Childhood cardiovascular risk factors in South Asians: A cause of concern for adult cardiovascular disease epidemic - Duggirala Sivaram Prasad; Zubair Kabir; Ashok Kumar Dash; Bhagabati Charan Das (Wolters Kluwer Medknow Publications, 2011)
Cardiovascular risk factors in children are increasing at an alarming rate in the western world. However, there is limited information regarding these in the South Asian children. This review attempts at summarizing such evidence. South Asians are remarkable for the earlier onset of adult cardiovascular disease (CVD) by almost a decade compared to the Caucasians. We identified published literature, mainly on PubMed, Embase and Cochrane library using specific search terms such as lipid abnormalities, high blood pressure, hyperglycemia, tobacco use, obesity, physical inactivity, and unhealthy dietary practices. Atherosclerotic CVD processes begin early in childhood and are influenced over the life course by genetic and potentially modifiable risk factors and environmental exposure. 80% of adult CVD burden will fall on the developing nations by 2020. The concept of primordial prevention is fast emerging as a necessary prevention tool to curb adult CVD epidemic. Established guidelines and proven preventive strategies on cardiovascular health exist; however, are always implemented half-heartedly. Composite screening and prediction tools for adults can be adapted and validated in children tailored to South Asian population. South Asian children could be at a greater risk of developing cardiovascular risk factors at an earlier stage, thus, timely interventions are imperative.